2006
DOI: 10.1203/01.pdr.0000246245.05530.02
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Expression of Glucocorticoid, Retinoid, and Thyroid Hormone Receptors Is Not Altered in Lungs of Congenital Diaphragmatic Hernia

Abstract: ABSTRACT:The degree of associated pulmonary hypoplasia and persistent pulmonary hypertension are major determination factors for survival in congenital diaphragmatic hernia (CDH) patients. Glucocorticoids, thyroid hormone, and vitamin A have been shown to be involved in human lung development. To determine their therapeutic potential in hypoplastic lungs of CDH patients, the temporal and spatial expression of glucocorticoid receptor, thyroid hormone receptors, retinoic acid receptors, and retinoid X receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
(52 reference statements)
3
18
0
Order By: Relevance
“…Quantitative PCR data showed that the expression of cellular binding protein mRNA was unaffected by nitrofen. Furthermore, the expression of RA receptor mRNA was not decreased, which is consistent with the report of Rajatapiti et al (55) from analyses of lung tissue in both the nitrofen model and human CDH. This, however, differs from a previous report of an almost complete abolition of Rar␣ and Rar␤ mRNA expression in nitrofen-exposed fetal mice (15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Quantitative PCR data showed that the expression of cellular binding protein mRNA was unaffected by nitrofen. Furthermore, the expression of RA receptor mRNA was not decreased, which is consistent with the report of Rajatapiti et al (55) from analyses of lung tissue in both the nitrofen model and human CDH. This, however, differs from a previous report of an almost complete abolition of Rar␣ and Rar␤ mRNA expression in nitrofen-exposed fetal mice (15).…”
Section: Discussionsupporting
confidence: 91%
“…Teramoto et al (61) reported a nitrofen-induced decrease expression of Tr␣1 and Tr␤1 in rat lungs compared with controls. However, a more recent study examining both nitrofen-exposed embryonic rat lung and human lungs from CDH cases reported no change in TR␣ and TR␤ protein or mRNA expression (55).…”
Section: Discussionmentioning
confidence: 94%
“…Nowadays, cells can be stored for a prolonged time, so cells derived from biopsies as well as the tissues itself could be stored to create a biobank for future research when new investigative techniques such as whole genome sequencing become available, or new results from animal studies warrant translation to the human situation. Our biobank of lung biopsy samples has proved to be an invaluable resource for many translational studies by our group, as demonstrated in the literature [13,14]. An example of the successful use of the biobank is the study by Rajatapiti et al [13], which demonstrated that the expression of glucocorticoid, retinoid and thyroid hormone receptors is not altered in lungs of patients with CDH.…”
Section: Discussionmentioning
confidence: 99%
“…Our biobank of lung biopsy samples has proved to be an invaluable resource for many translational studies by our group, as demonstrated in the literature [13,14]. An example of the successful use of the biobank is the study by Rajatapiti et al [13], which demonstrated that the expression of glucocorticoid, retinoid and thyroid hormone receptors is not altered in lungs of patients with CDH. This is especially important in diseases such as CDH in which survival has improved (and therefore the opportunity to obtain material from deceased patients has become rare), but there is still a need for elucidating the exact pathogenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation